2021
DOI: 10.1136/bmjgh-2021-005238
|View full text |Cite
|
Sign up to set email alerts
|

Optimising geographical accessibility to primary health care: a geospatial analysis of community health posts and community health workers in Niger

Abstract: BackgroundLittle is known about the contribution of community health posts and community health workers (CHWs) to geographical accessibility of primary healthcare (PHC) services at community level and strategies for optimising geographical accessibility to these services.MethodsUsing a complete georeferenced census of community health posts and CHWs in Niger and other high-resolution spatial datasets, we modelled travel times to community health posts and CHWs between 2000 and 2013, accounting for training, co… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
40
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
2

Relationship

3
3

Authors

Journals

citations
Cited by 19 publications
(46 citation statements)
references
References 25 publications
1
40
0
Order By: Relevance
“…A DNO could potentially give different results if the demand side is modelled based on population alone or the epidemiology of the target disease. A recent study using malaria incidence in Niger demonstrated that this is the case when modelling the deployments of community health workers [ 14 ]. To summarize, physical accessibility modeling can improve RO by providing accurate information on travel scenarios and times, as well as on barriers to movement.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A DNO could potentially give different results if the demand side is modelled based on population alone or the epidemiology of the target disease. A recent study using malaria incidence in Niger demonstrated that this is the case when modelling the deployments of community health workers [ 14 ]. To summarize, physical accessibility modeling can improve RO by providing accurate information on travel scenarios and times, as well as on barriers to movement.…”
Section: Discussionmentioning
confidence: 99%
“…Although these analyses typically do not include costs, accurate transport modes and speeds determined by experts in the field provide better estimates of parameters for accessibility models [ 9 , 10 ]. Such approaches have also been used to model population accessibility to health services, such as primary healthcare [ 11 ], emergency obstetric and neonatal care [ 12 , 13 ], and community health services [ 14 ]. Although this dimension is not currently part of the DNO, it may provide an interesting additional functionality that could be added in the future.…”
Section: Introductionmentioning
confidence: 99%
“…5,18,[23][24] However only three previous studies have used geospatial analysis to assess the efficiency of CHW deployment at national scale using robust modelling approaches. [20][21][22] Champagne et al compared the efficiency of various CHW deployment scenarios in terms of optimising geographic coverage of the estimated population in Haiti. 22 five deaths, and Pf malaria cases, respectively, and found that the existing CHW networks were inefficiently deployed across all three targeting metrics.…”
Section: Discussionmentioning
confidence: 99%
“…18 This deficit is exacerbated by a maldistribution of HRH, including CHWs, with the most severe effects in Africa, particularly in rural, remote, and under-served geographic areas. [18][19][20][21] As countries strive to increase sustainable financing for HRH, including for CHWs, concurrent efforts are needed to maximize the impact and efficiency of available funding through optimising the scale and deployment of HRH. Global strategies and frameworks from the WHO call for optimising the distribution of HRH and geographical accessibility to integrated PHC services.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation